Strategi Inovatif Mengembangkan Berpikir Kritis: Proyek Site Plan Berbasis Google My Maps - Erlangga, Dimas; Ningrum, Epon; Nandi, Nandi (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
21st-century learning requires students to have critical thinking skills essential in the era of globalization. The purpose of the study is to examine the influence of the use of the Google My Maps-based Site Plan project on students' critical thinking skills at SMA Negeri 1 Jatiwangi. Quasi-experimental research method with a non-equivalent control group design, this study involved class XII IPS-3 as an experiment and XII IPS-2 as a control. Data analysis was carried out through statistical tests such as normality, homogeneity, Wilcoxon, N-Gain, Mann-Whitney, and simple linear regression tests. The results showed that the experimental class experienced an increase in critical thinking skills with an N-Gain of 0.44 (medium category), compared to the control class which only achieved an N-Gain of 0.26 (low category). Significant differences were found between the two classes, with a Google My Maps-based project contributing 62% to the improvement of critical thinking skills. It is recommended that the process of creating a project is accompanied by intensive monitoring.